Analisis Kinerja Keuangan Sektor Perbankan Sebelum dan Sesudah Adanya Perusahaan Teknologi Finansial - Raysa Azahra Ade Putri; Dewi Cahyani Pangestuti; Agus Kusmana (Reviu Akuntansi, Manajemen, dan Bisnis, 2021)
Purpose: The intention of the research was to examine if there were any discrepancies in banks ’ financial performance before and after the introduction of financial tech firms. Research Methodology: The study's subject was registered banking on the Indonesia Stock Exchange (IDX), with 38 banks chosen as a sample over a two-year period before the introduction of financial tech firms (2013-2014) and two years after the existence of financial tech firms (2016-2017). With a 5% significance rate, the tests utilized in this paper were Paired Sample T-test (normal data) and Wilcoxon Sign Rank Test (abnormal data) with SPSS 25 software assistance. Results: The outcomes of this research, after the arrival of financial technology enterprises, there is a discrepancy in profitability, liquidity, and capital. Limitations: This research's limitations are that certain banks did not leak consecutive financial statements during the research period, and earlier studies had no specific explanation on the same topic. Contribution: The insights can be used by academics as a reference, by the Bank as a foundation for financial management innovation, and by investors as a source of knowledge and consideration when making investment decisions.